A quantum photonic chip for binary classification - Lin, H. X. (Institutional Knowledge at Singapore Management University, 2023)
On the silicon photonic chip, we apply Mach Zehnder Interferometer (MZI) and optical network to manipulate the phase difference and amplitude distribution of the input light. The two or three-dimensional input data is encoded in the light amplitude distribution and the genetic algorithm is applied to update the angle parameters of the MZIs to improve the classification result.